Service-Learning in Science Instruction (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2018)
As the addage goes "Tell me and I forget. Teach me and I may remember. Involve me and I learn," states that students must be engaged actively in learning for them to achieve meaningful learning. Service-learning is a teaching pedagogy that enables students to transfer knowledge and skills learned in the classroom to meaningful service in the community. This quasi-experimental research investigated the effectiveness of the Service-Learning pedagogy, which is said to be a strategy to realize the concept of “practical life" experiences. Using the total enumeration method, 30 students went through a pretest and posttest in the Environmental Science subject. The same set of students was immersed in the service-learning activities. Along the tests conducted, students were also rated in their formative evaluation after conducting the activities. Results showed that the environmental science knowledge of students differ significantly after conducting the service-learning activities. Further results showed that students were rated Superior in their formative evaluation. Thus, Service-learning activities are effective in increasing the knowledge of students on environmental science topics.
Keywords: service-learning, environmental science instruction